Monday

March 30, 2015

March 30, 2015

Posted by **Jesse Stone** on Friday, January 27, 2012 at 9:29am.

NOTE:

that logx is a sub x

- Calculus -
**Reiny**, Friday, January 27, 2012 at 11:21amlet y = log

_{x}(x^2 - 5x + 6)

x^y = x^2 - 5x + 6

ln both sides

ln (x^y) = ln(x^2 - 5x + 6)

y lnx = ln(x^2 - 5x + 6)

differentiate implicityly

y(1/x) + (lnx) dy/dx = (2x-5)/(x^2-5x+6)

dy/dx = ((2x-5)/(x^2-5x+6) - y/x)/lnx

**Answer this Question**

**Related Questions**

math - I tried everthing but,I couldnt solve it. Please help me.the answer at ...

Calculus - If y=Root of(logx+root of (logx+root of logx.........infinty)...prove...

algebra - If LOGx (A)=0.7 and LOGx (B) =0.5 how do I solve LOGx (B/A)

Math - these are some problems i do not get any help is appreciated. These are ...

^Maths^ - If Logx-6 base3=2y and Logx-7 base2=3y, show that x^2-13x+42=72y

pre calculous - solve each equation algebraically and check it by substituing ...

Logarithms - I need help evaluation the following: 1.) (1/15)^2.309 It says hint...

Calculus - Following 2 questions are from a book at a point where L’Hopital’s ...

Calculus - Following 2 questions are from a book at a point where L’Hopital’s ...

MATHS - If e^(x+3logx) then prove that dy/dx=x^2(x+3)e^x....can anyone help me ...